Exact solutions of steady-state dynamic responses of a laminated composite double-beam system interconnected by a viscoelastic layer in hygrothermal environments. (15th July 2021) - Chen, Bo; Lin, Baichuan; Li, Yinghui; Tang, Huaiping
Abstract: The current paper is the first to study the steady-state dynamic problem of a laminated composite double-beam system (LCDBS) under hygrothermal environments, in a systematic manner. The LCDBS consists of two laminated composite beams connected by a uniformly distributed viscoelastic layer and is supported on the Winkler-Pasternak elastic foundation. The governing equations of LCDBS are derived based on the Euler–Bernoulli beam hypothesis considering the free expansion caused by temperature variation and moisture concentration. Exact solutions for steady-state dynamic responses of the LCDBS are obtained by employing the Green's functions method and superposition principle. In the meantime, the implicit equation calculating the natural frequency of the LCDBS is proposed. The material properties are considered to be temperature- and moisture-dependent. Numerical calculations are performed to explore the influences of physical parameters of the connecting layer, foundation stiffness, fiber orientation angle, temperature variation, and moisture concentration on steady-state dynamic responses of the LCDBS. Outcomes reveal that the bond between the two beams can be strengthened by increasing the stiffness and damping coefficient of the connecting layer, and the increase of the temperature variation can significantly reduce the system stiffness and enhance the dynamic responses of the two beams.